Pneumocystis jirovecii in HIV patients and suspected pneumonia: a problematic diagnosis in Caracas, Venezuela. / Pneumocystis jirovecii en pacientes con infección por el VIH y sospecha de neumonía: un diagnóstico problemático en Caracas, Venezuela. - Panizo, María Mercedes; Ferrara, Giuseppe; García, Nataly; Reviakina, Vera; Navas, Trina; Moreno, Xiomara; Capote, Ana María; Dolande, Maribel; Alarcón, Víctor; Calderón, Enrique (Investigación Clínica, 2021)
Abstract. Pneumocystis jirovecii pneumonia (PCP) is one of the most frequent opportunistic infections in immunocompromised patients. The objective of this study was to know the P. jirovecii epidemiology in Venezuelan patients with Human Immunodeficiency Virus (HIV) infection and suspected pneumonia, through passive surveillance at a national reference laboratory during six years. Laboratory records of patients with HIV infection, who were hospitalized with acute lower respiratory tract infection (ALRTI), and presumptive clinical diagnosis of PCP, were reviewed between January 2007 and December 2012, at the Mycology Department of the Instituto Nacional de Higiene Rafael Rangel. Several respiratory specimens were received and the direct immunofluorescence assay (DIF) and nested polymerase chain reaction (nPCR) diagnostic techniques were used. One hundred and sixty-one respiratory samples were processed and P. jirovecii was detected in 76 samples by DIF and in 20 by nPCR. PCP’s frequency in Venezuelan patients with HIV is high and it has been sustained throughout time. Colonization by P. jirovecii has uncertain clinical significance, but this study provides evidence that the state of advanced immunosuppression increases the probability of colonization. DIF and nPCR are very useful techniques for PCP diagnosis, but are of limited access in many hospital centers, especially in developing countries. We recommend the use of DIF with spontaneous sputum specimens as the first diagnostic line for PCP in patients with HIV infection. The results obtained by nPCR should be interpreted with caution, taking into account the patient’s clinical symptoms.Resumen. La neumonía por Pneumocystis jirovecii (PCP) es una de las infecciones oportunistas más frecuente en pacientes inmunocomprometidos. El objetivo de este trabajo fue conocer la epidemiología del P. jirovecii en pacientes venezolanos con infección por el Virus de Inmunodeficiencia Humana (VIH) y sospecha de neumonía, mediante vigilancia pasiva en un laboratorio de referencia nacional durante un período de 6 años. Se revisaron los registros de laboratorio de los pacientes con infección por el VIH hospitalizados con Infección Aguda del Tracto Respiratorio Inferior (IATRI) y diagnóstico clínico presuntivo de PCP, entre enero de 2007 a diciembre de 2012 en el Departamento de Micología del Instituto Nacional de Higiene Rafael Rangel. Se recibieron diversas muestras del tracto respiratorio y los métodos diagnósticos empleados fueron inmunofluorescencia directa (IFD) y reacción en cadena de la polimerasa anidada (nPCR). Se procesaron 161 muestras respiratorias y se detectó P. jirovecii en 76 muestras por IFD y en 20 por nPCR. La frecuencia de PCP en pacientes venezolanos con HIV es elevada y se ha mantenido en el tiempo. La colonización por P. jirovecii tiene un significado clínico incierto, pero este estudio aporta evidencia de que un estado avanzado de inmunosupresión incrementa la probabilidad de colonización. La IFD y la nPCR son técnicas muy útiles para el diagnóstico de la PCP, pero son de acceso limitado en muchos centros hospitalarios, sobre todo en países en vías de desarrollo. Recomendamos la utilización de la IFD con muestras de esputo espontáneo como primera línea de diagnóstico para la PCP en pacientes con VIH. Los resultados obtenidos por nPCR deben ser interpretados tomando en cuenta la sintomatología clínica del paciente.